Concentrations of Cu, Fe, Mn, and Zn in tropical soils amended with sewage sludge and composted sewage sludge - Nogueirol, Roberta Corrêa; De Melo, Wanderley José [UNESP]; Bertoncini, Edna Ivani; Alleoni, Luís Reynaldo Ferracciú (Springer Nature, 2013)
Sewage sludge may be used as an agricultural fertilizer, but the practice has been criticized because sludge may contain trace elements and pathogens. The aim of this study was to compare the effectiveness of total and pseudototal extractants of Cu, Fe, Mn, and Zn, and to compare the results with the bioavailable concentrations of these elements to maize and sugarcane in a soil that was amended with sewage sludge for 13 consecutive years and in a separate soil that was amended a single time with sewage sludge and composted sewage sludge. The 13-year amendment experiment involved 3 rates of sludge (5, 10, and 20 t ha-1). The one-time amendment experiment involved treatments reflecting 50, 100, and 200 % of values stipulated by current legislation. The metal concentrations extracted by aqua regia (AR) were more similar to those obtained by Environmental Protection Agency (EPA) 3052 than to those obtained by EPA3051, and the strongest correlation was observed between pseudo(total) concentrations extracted by AR and EPA3052 and bioavailable concentrations obtained by Mehlich III. An effect of sewage sludge amendment on the concentrations of heavy metals was only observed in samples from the 13-year experiment. © 2012 Springer Science+Business Media B.V.
Keywords: Digestion methods; Extractants; Heavy metals; Residuals; Bioavailable concentrations; Composted sewage sludges; Digestion method; Metal concentrations; Sludge amendment; Tropical soils; Environmental Protection Agency; Experiments; Manganese; Soils; Zinc; Sewage sludge; copper; iron; manganese; zinc; heavy metal; bioavailability; concentration (composition); maize; residual soil; sewage; sludge; soil pollution; sugar cane; tropical soil; comparative effectiveness; composting; concentration (parameters); controlled study; correlation analysis; leaching; soil amendment; soil analysis; sugarcane; tropics; agriculture; Brazil; chemistry; environmental monitoring; pollution; soil; soil pollutant; statistics; Zea mays; Agriculture; Copper; Environmental Monitoring; Environmental Pollution; Iron; Metals, Heavy; Sewage; Soil; Soil Pollutants; Waste Disposal, Fluid